Bluetooth-based alarm system - Abd Wahab, Mohd Helmy; Md Janah, Nor Ezna Juniza; Johari, Ayob; Md Nor, Danial; Sanudin, Rahmat (2009)
This paper proposes the implementation and the advantage of Bluetooth technology on wireless alarm system.The system is realized using a microcontroller PIC16F877A and MPLab IDE software as the control block to link between input and output signals. This paper is using both Bluetooth adapter and Bluetooth module to manipulate the command given to the system.In fact, the traditional 32-bit alarm security system seems dwarfed by this wireless alarm system due to its high security, more user-friendly and lower-cost.Moreover, this wireless technology could operate within a distance of up to 10m independent of line of sight even with obstacles in between.The result shows the wireless system could control intended output with no trouble within specified distance. Hence, it is concluded that the system works effectively with more improvement over the conventional system.